The Acidophilic Methanotroph Methylacidimicrobium tartarophylax 4AC Grows as Autotroph on H2 Under Microoxic Conditions - Mohammadi, Sepehr S.; Schmitz, Rob A.; Pol, Arjan; Berben, Tom; Jetten, Mike S. M.; Op den Camp, Huub J. M. (Frontiers in Microbiology, 2019)
Emissions of the strong greenhouse gas methane (CH¬4) to the atmosphere are mitigated by methanotrophic microorganisms. Methanotrophs found in extremely acidic geothermal systems belong to the phylum Verrucomicrobia. Thermophilic verrucomicrobial methanotrophs from the genus Methylacidiphilum can grow autotrophically on hydrogen gas (H2), but it is unknown whether this also accounts for their mesophilic counterparts from the genus Methylacidimicrobium. To determine this, we examined H2 consumption and CO2 fixation by the mesophilic verrucomicrobial methanotroph Methylacidimicrobium tartarophylax 4AC. We found that strain 4AC grows autotrophically on H2 with a maximum growth rate of 0.0048 h-1 and a yield of 2.1 g dry weight · mol H2-1, which is about 12 % and 41 % compared to the growth rate and yield on methane, respectively. The genome of strain 4AC only encodes for an oxygen-sensitive group 1b [NiFe] hydrogenase and H2 is respired only when oxygen concentrations are below 40 µM. Phylogenetic analysis and genomic comparison of methanotrophs revealed diverse [NiFe] hydrogenases, presumably with varying oxygen sensitivity and affinity for H2, which could drive niche differentiation. Our results show that both thermophilic and mesophilic verrucomicrobial methanotrophs can grow as autotrophs on H2 as sole energy source. Our results suggest that verrucomicrobial methanotrophs are particularly well-equipped to thrive in hostile volcanic ecosystems, since they can consume H2 as additional energy source.